Intraprocedural Stent Thrombosis During Percutaneous Coronary Intervention: How to Predict - Bayu Aji; Mohammad Saifur Rohman; Budi Satrijo; Arief Wibisono (Heart Science Journal, 2022)
Background: Intraprocedural stent thrombosis (IPST) during percutaneous coronary intervention (PCI) is an uncommon event that results in a poor outcome including STEMI and sudden cardiac death. Concerns about an increased risk of stent thrombosis with drug-eluting stents (DES) continue, even though the incidence, timing, and predictors of stent thrombosis with DES have not been identified.Objective: This study aimed to describe the diagnosis and management of Intraprocedural Stent Thrombosis.Case presentation: We will discuss a 49 year-old male brought to our hospital because of chest pain while doing moderate activity. One month prior to admission, he had history of acute coronary syndrome and 1 DES on right coronary artery was placed. Ticagrelor and aspirin were routinely consumed as dual antiplatelet therapy. The patient was diagnosed with intraprocedural stent thrombosis during PCI with the evidence of intra-catheter thrombosis and ST segment elevations seen in the ECG monitor. We treat the patient with Ticagrelor 180 mg loading dose and intracoronary unfractionated heparin (UFH) during procedure continued with continuous infusion until 24 hours. No event of subsequent acute coronary syndrome was observed.Conclusion: Intraprocedural Stent Thrombosis was a strong predictor of mortality in STEMI patients. This case showed that the present widespread use of DES instead of BMS for coronary implantation although decreased the future risk of repeat revascularization, increased the risk of thrombosis. Prior risk stratification, potent early antiplatelet treatment and anticoagulant of choice with UFH might be used to reduce the risk of thrombosis in STEMI patients undergoing stent implantation.